Allergy, inflammation, hepatopathy and coagulation biomarkers in dogs with suspected anaphylaxis due to insect envenomation - Turner, Kate; Boyd, Corrin; Rossi, Gabriele; Sharp, Claire R.; Claus, Melissa A.; Francis, Abbie; Smart, Lisa (Frontiers in Veterinary Science, 2022)
Objectives: To compare concentrations of biomarkers of; allergy (mast cell tryptase [MCT] and histamine), inflammation (interleukin[IL]-6,-10, and -18, CXCL8, CCL2, keratinocyte chemoattractant [KC], C-reactive protein [CRP]), glycocalyx shedding (hyaluronan), coagulation (prothrombin time, activated partial thromboplastin time, fibrinogen concentration, and von Willebrand Factor antigen, protein C [PC] and antithrombin [AT] activity), and hepatopathy between dogs with anaphylaxis after suspected insect exposure, dogs with critical illness, and healthy dogs. Design: This was a single center prospective clinical observational comparative biomarker study that included 25 dogs with anaphylaxis (evidence of insect exposure, acute dermatological signs, and other organ involvement), 30 dogs with other critical illness that required a fluid bolus, and 20 healthy dogs. Differences across groups in biomarker concentrations were tested using one-way ANOVA or Kruskal-Wallis test, with significant P values (<0.05) reported for pairwise differences detected by either a Tukey-Kramer or Dwass-Steel-Critchlow-Fligner test. Univariate logistic regression models were used to calculate the area under the receiver operator characteristic curve (AUROC) for discrimination between anaphylaxis and non-anaphylactic illness. Results: Histamine concentration was significantly higher in the anaphylaxis group than the healthy (P<0.001) and critically ill groups (P<0.001), whereas no differences in MCT were detected amongst groups. Biomarker concentrations that were increased relative to healthy dogs in both the anaphylaxis and critically ill groups included IL-10 (P<0.001 and P=0.007, respectively), CCL2 (P=0.007 and P<0.001, respectively) and aspartate aminotransferase (both P<0.001), whereas only the critically ill group had significantly increased CRP (P<0.001), IL-6 (P<0.001), KC (P<0.001), alkaline phosphatase (P<0.001), and fibrinogen (P=0.016) concentrations, compared to the healthy group. Only dogs with anaphylaxis had significantly higher hyaluronan (P=0.021) and alanine transferase (P=0.021) concentrations, and lower PC (P=0.030) and AT (P=0.032) activities, compared to healthy dogs. Both CRP and histamine concentration showed good discrimination between anaphylaxis and other critical illness, with an AUROC of 0.96 (95% CI 0.91-1) and 0.81 (95% CI 0.69-0.93), respectively. Conclusions: This preliminary study in dogs with anaphylaxis after suspected insect exposure, found evidence of an early innate immune response, glycocalyx shedding and anticoagulant consumption. Both CRP and histamine showed potential clinical utility for differentiation between anaphylaxis and other critical illness.